The Influence of Product Quality, Location and Word of Mouth on Purchase Decisions - Hartatik, Hartatik; Mendrofa, Syah Abadi; Mar'ati, Fudji Sri; Wicahyono, Agus; Permana, Indra (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The research analysis aims to determine the effect of product quality, location and word of mouth (WOM) on purchasing decisions at Bebek Goreng Pak Slamet. The sampling collection used was purposive sampling of 100 respondents. Data collection used a questionnaire distributed to customers at Bebek Goreng Pak Slamet. The population in this study were customers of Bebek Goreng Pak Slamet. This research method uses quantitative methods and multiple linear regression analysis through SPSS 24. The results of this study indicate that product quality, location and word of mouth (WOM) have a positive and simultan impact on purchasing decisions at Bebek Goreng Pak Slamet.